IMPROVEMENT OF CRITICAL THINKING ABILITY AND LEARNING INTEREST MATHEMATICS USING MODELS PROBL EM BASED LEARNING ON STUDENT CLASS V SD IT NURUL ILMI PADANG SIDEMPUAN - Parkumpulan Siregar; Armanto Armanto; Zulkifli Matondang (Sensei International Journal of Education and Linguistic, 2023)
The purpose of this research is to improve students' critical thinking skills and interest in learning mathematics Class V SD IT Nurul Ilmi Padang Sidempuan . Using the Problem learning model based Learning can improve critical thinking skills and interest in learning mathematics. Improvement from pre cycle, cycle I, and cycle II based on the criteria of critical thinking and completeness of interest in learning. Obtained increased student learning interest, the acquisition of the average grade of the student class increase that is on pre cycle is 51.5 , on cycle I increase become 71 , 2 and in cycle II it increased again to 77.5 during the pre-cycle 13 students ( 21.6 %) who completed, in cycle I became 29 students ( 48.3 %) who completed, and on cycle II Also happen enhancement become 46 student (7 6 ,7%) Which complete. Meanwhile, students who had not completed the pre-cycle were 47 students ( 7.8.3 %) did not complete, in cycle I decreased to 31 students ( 51.6 %) who did not complete, And on cycle II Also experience decline become 15 student (2 3 , 3 %) Which No complete. Whereas For ability think critical student show that level students' critical thinking abilities can be seen starting from the pre-cycle and cycle I reached 2 students or 1 6,7 %, whereas enhancement from cycle I And cycle II reach 9 student or 31.6 %. On level currently obtained enhancement from pre cycle And cycle I as much as 7 person or 31.6 %, whereas from cycle I And cycle II experience an increase of 7 (43,3%).